Protein blocks for gestating beef cows wintered on bluestem pasture: soybean meal and starea compared - Shiawoya, E.L.; Harbers, L.H.; Evans, J.D.; McKee, R.M (Kansas State University. Agricultural Experiment Station, 2011)
Pregnant Hereford and Angus cows wintered on native bluestem pasture were used to compare soybean-meal and Starea-containing blocks and protein supplements. Cow weight changes were similar with both supplements. Consumption of Starea supplement declined throughout the trial, while soybean meal block consumption remained constant.
Keywords: Beef; Protein; Bluestem pasture; Soybean meal; Starea